E-Commerce Competence Assessment Mobile Application Development for SMEs in Thailand - Wongkhamdi, Thipsuda; Cooharojananone, Nagul; Khlaisang, Jintavee (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The objectives of this study are to develop e-Commerce self-assessment application based on research and to evaluate the adoption of the system by using the Technology Acceptance Model (TAM) which are designed for SMEs self-assessment and the government agencies are able to retrieve the report. The system development deployed Microsoft .NET CORE Technology with C# language, HTML/CSS/JS for Mobile Web Development. All data will store on Aurora RDS. The web deployed on Amazon public cloud that will automatic scale when a lot of traffic arrived. Since the indicators from the research have been developed as an application, users will be able to use it conveniently anytime and anywhere. The system will help entrepreneurs realize the level of ecommerce knowledge of their own in various areas and help them to know what needs to be improved and more importantly, government officials can allocate budget for training in order to improve entrepreneurs’ performance. The evaluation result of system adoption in 30 cosmetic and supplementary food entrepreneurs showed that for Perceive Usefulness, the use of application systematically revealed the strength, weakness and potential of themselves and was beneficial for self-assessment in online selling skills, xÌ„ = 4.50 equally. Perceived Ease of Use, it is very easy to do self-assessment through application, xÌ„ = 4.63. Attitude Toward Using, in general, the attitude toward using the application was positive, xÌ„ = 4.73. Behavioral Intention to Use, the intention to use this application in the future, xÌ„ = 4.57 and 100% of 30 respondents were interested to use the system.